(untitled) (ModaPalavra e-periódico, 2022)
This study aims to reflect on a possible symbiosis between the fashion system and unrelated companies focused on reducing textile waste. Recent developments in the fashion system, in terms of the organizational network, highlight the importance of collaboration, or vice versa of competition enhancement mechanisms. The highly innovative and creative skills and tasks concentrate much of the value in the creation phase, characteristic of emerging sectors such as creative ones. The methodology will be carried out through a review of the reference literature, with a critical, constructive, and real analysis on strategies for the construction of this symbiosis. It is expected to contribute to a reflection on the development of collaboration and cooperation skills in an interdisciplinary, or even transdisciplinary approach, for the training and preparation of fashion design professionals, requiring a greater commitment from Academia in the creation of interactions and interrelationships with still very different disciplinary sectors.